2017
DOI: 10.1038/srep46834
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Enzyme discovery beyond homology: a unique hydroxynitrile lyase in the Bet v1 superfamily

Abstract: Scientific Reports 7: Article number: 46738; published online: 03 May 2017; updated: 26 May 2017 The original version of this Article contained errors. In the Introduction section, “Finally there is a number of characterized HNLs with yet unpublished amino acid sequences and protein folds, for example, PatHNL (Prunus amygdalus turcomanica)25, ParsHNL (Prunus armeniaca L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Therefore, this mutation and the corresponding substructural changes in the landscape of the active site of OgraHNL may be responsible for the enhanced conversion of BA and C–2 substituted benzaldehydes and ee of ( R )‐Man and ( R )‐2‐Cl−Man. Interestingly, the Ala97 residue is located in a region conserved among cyanogenic millipede HNLs [3e] . Thus, the findings presented in this work are expected to be valuable with respect to mutations for improved enzyme catalytic activity and/or enantioselectivity, by suggesting avenues for engineering other millipede HNLs.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Therefore, this mutation and the corresponding substructural changes in the landscape of the active site of OgraHNL may be responsible for the enhanced conversion of BA and C–2 substituted benzaldehydes and ee of ( R )‐Man and ( R )‐2‐Cl−Man. Interestingly, the Ala97 residue is located in a region conserved among cyanogenic millipede HNLs [3e] . Thus, the findings presented in this work are expected to be valuable with respect to mutations for improved enzyme catalytic activity and/or enantioselectivity, by suggesting avenues for engineering other millipede HNLs.…”
Section: Resultsmentioning
confidence: 80%
“…We recently reported the X‐ray structures of new HNLs from the millipedes C. hualienensis [2c] and Parafontaria laminata [2d] belong to the lipocalin‐like fold. The HNLs identified to date can be classified into seven superfamilies [3a] that include lipocalin, glucose–methanol–choline (GMC) oxidoreductase, [3b] α/β‐hydrolases, [3c,d] cupin, [3e] Bet v1, [3f] dimeric α+β barrel folds, [3g] and Zn 2+ ‐dependent alcohol dehydrogenase [3]…”
Section: Introductionmentioning
confidence: 99%
“…The first HNL of Bet v1 superfamily was discovered from the fern Davallia tyermannii (DtHNL) by a combination of transcriptomics, proteomics and enzymatic screening studies. [29] Mass spectrometry data of proteins from D. tyermannii leaves with HNL activity were analyzed by searching the translated D. tyermannii transcriptome that helped to uncover four DtHNL isoenzyme genes. The four genes identified corresponding to the ORFs, isotig02643, 02641, 07602 and contig00751 named DtHNL1, DtHNL2, DtHNL3 and DtHNL4, respectively were amplified from D. tyermannii gDNA by PCR, cloned and expressed in E. coli.…”
Section: Asymmetric Synthesis Using Natural Nucleophile (Cyanide)mentioning
confidence: 99%
“…higher acid tolerance and specific activity than the WT higher % conv. and ee than the WT towards hydrocyanation of 4methylthiobenzaldehyde [39] DtHNL Gibson assembly method D85A, S87A, Y101F, Y117F, Y161F and D85S-S87D resulted in inactive mutants, decreased the activity by at least 90 %., produced insoluble protein and prevented activity measurements [29] PeHNL SDM PeHNL-P-N105Q poor thermostability, pH stability, organic solvent tolerance, and enantioselectivity than the WT [40] PeHNL SDM PCR followed by cloning H8A, Y30F, E54A, E54Q, R56A, S66A, N101A and N101D PeHNL~107 reduced activity for cleavage and synthesis of (R)-MN than the WT increased activity for cleavage and synthesis of (R)-MN than the WT [41] PeHNL PCR followed by cloning PeHNL~107 improved stability, conv. and enantiselectivity in synthesis of nine (R)cyanohydrins [42] ChuaHNL-PpPDI SDM N99Q, N109Q, N123Q, N99Q-N109Q, N99Q-N123Q and N109Q-N123Q N123Q low protein production revealed that sugar chains are essential for the high-level production in His-ChuaHNL higher specific activity towards three of the eight aromatic aldehydes in their chiral cyanohydrin synthesis [43] ChuaHNL SDM R38A, Y40F, D56E, Y103F and K117R lost or decreased activity in cyanogenesis and cleavage of (R)-MN [44] PlamHNL SDM PlamHNL-N85Y higher enantioselectivity and conv.…”
Section: Enantioselective Cleavagementioning
confidence: 99%
See 1 more Smart Citation